Associations between visual-motor integration, pencil grip patterns, and holistic academic performance among school children - Naufal Nordin; Woi Pui Juan; Nurul Umira Samsudin (PLoS ONE, 2026)
Background Visual-motor integration (VMI) is a key developmental skill that supports children’s daily classroom tasks and academic readiness. This study examined the associations between VMI components, pencil grip patterns, and holistic academic performance among Malaysian primary school children. Materials and Methods A total of 148 children (mean age = 9.94 ± 1.78 years) from three urban schools in Kuala Lumpur were assessed. VMI, visual perception, and motor coordination were measured using the Beery-Buktenica Developmental Test of Visual-Motor Integration (Beery-VMI). Pencil grip patterns were classified into five types using standardized photographs taken during the Beery-VMI assessment. Academic mastery in Malay Language, English, Science, and Mathematics was obtained from the Classroom-Based Assessment (CBA) system, which reflects holistic and continuous teacher-based evaluations. Results Beery-VMI raw scores were significantly associated with CBA academic performance across all four core subjects, with the strongest correlations observed for Science (ρ = 0.332, p < 0.001) and Mathematics (ρ = 0.284, p < 0.001). Beery-VMI standard scores remained significantly associated only with Science (ρ = 0.305, p < 0.001) and Mathematics (ρ = 0.219, p = 0.008). This pattern suggests that raw scores reflect both VMI performance and age-related developmental factors relevant to academic performance, whereas standard scores provide age-adjusted estimates. Age significantly predicted VMI standard scores, accounting for 14% of the variance (R² = 0.140), with older children in this sample showing lower age-adjusted scores. Pencil grip differences were significant for VMI raw scores (χ² = 9.74, p = 0.045), with the lateral quadrupod grip demonstrating the highest performance. Conclusion VMI was associated with academic mastery, especially in Science and Mathematics. Raw scores may reflect shared development, while standardized scores suggest a more specific age-independent link between VMI and academic performance. Pencil grip patterns showed limited association with VMI outcomes and may not strongly indicate visual-motor performance.